EFFECTIVE METHODS FOR DEVELOPING LISTENING COMPREHENSION - Dadaboyeva Fayyoza Khikmatulloyevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The development of listening comprehension is important for improving communication skills and receiving information correctly. This article analyzes effective ways to improve listening skills. In particular, it has been shown that listening comprehension skills can be developed by focusing, using active listening techniques, analyzing what is heard, reconfirming what has been understood, and regular self-assessment.